The optimal resource allocation in stochastic activity networks via the evolutionary approach : a platform implementation in Java - Tereso, Anabela Pereira (2007)
An optimal resource allocation approach to stochastic multimodal projects had been previously developed by applying a Dynamic Programming Model, which proved to be very demanding computationally. A new approach, the Electromagnetism Algorithm had also been adapted and implemented, with better results than the Dynamic Programming Model. This paper presents another philosophy for solving the same problem, based on an Evolutionary Algorithm. This approach was implemented using an Object Oriented language, Java, and its results were compared to the Electromagnetism Algorithm. A distributed version was also developed, to be run in a computer network, in order to take advantage of available computational resources.